2015
DOI: 10.1159/000430273
|View full text |Cite
|
Sign up to set email alerts
|

The Chemopreventive Effect of Tanacetum Polycephalum Against LA7-Induced Breast Cancer in Rats and the Apoptotic Effect of a Cytotoxic Sesquiterpene Lactone in MCF7 Cells: A Bioassay-Guided Approach

Abstract: Background: Tanacetum polycephalum L. Schultz-Bip is a member of the Asteraceae family. This study evaluated the chemopreventive effect of a T. polycephalum hexane extract (TPHE) using in in vivo and in vitro models. Methods and Results: Five groups of rats: normal control, cancer control, TPHE low dose, TPHE high dose and positive control (tamoxifen) were used for the in vivo study. Histopathological examination showed that TPHE significantly suppressed the carcinogenic effect of LA7 tumour cells. The tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Cyclin-dependent kinase p21 is tumor suppressor, which promotes cell cycle arrest, blocks cell division, and down-regulation of p21 often occurs in breast cancer [31]. Recent studies have demonstrated that p21 involved in anti-tumor progression in breast cancer, and anti-tumor drug increased p21 expression which led to breast cancer cell apoptosis [32,33]. p73 and p21 can promote anti-proliferation activity and induce apoptosis by p53-independent mechanisms [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase p21 is tumor suppressor, which promotes cell cycle arrest, blocks cell division, and down-regulation of p21 often occurs in breast cancer [31]. Recent studies have demonstrated that p21 involved in anti-tumor progression in breast cancer, and anti-tumor drug increased p21 expression which led to breast cancer cell apoptosis [32,33]. p73 and p21 can promote anti-proliferation activity and induce apoptosis by p53-independent mechanisms [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Interruption or malformation of the cell plasma membrane which is a common property of cancer cells causes the cell construction losing and break of their life cycle [ 39 ]. Phosphatidylserine (PS) translocation from the inner side of the plasma membrane to the outer side of the plasma membrane is a typical marker of early apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 2E also shows that the cell population in S phase decreased from 26.81% to 6.77%, while the percentage of the population in G2/M phase decreased from 20.01% to 3.41%. The cyclin-dependent kinases (CDKs) have a critical role in cell cycle control through their interaction with cyclins and Cdk inhibitors (CKIs) [ 39 ]. The irregular growth of cancer cells is associated with the abnormal activity of CKIs.…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer is the most common malignancy among women presenting an emerging major health problem around the world and the number of cases of has increased dramatically in Asia over the past few decades [1][2][3][4] . The development drug resistance in breast cancer is a growing challenge in the field of cancer therapy.…”
Section: Research Papermentioning
confidence: 99%